Lean Manufacturing Approach as A Means of Improving Callaway Diablo Golf Glove Production Systems - Pujo Saroyo; Kun Farihah; Mahmudun Ainuri (APTA and DTIP FTP UGM, 2017)
This study was aimed to provide suggestions for improvement of the value stream, which was illustrated using Value Stream Mapping through the reduction of wastes. The measure of improvement was focused on the process cycle efficiency (PCE) of the Callaway Diablo golf glove production systems at Adi Satria Abadi limited company. At the initial condition of Value Stream Mapping, the identified wastes were inventories, delays, transports, and defects. Those four wastes were then mapped using Value Stream Analysis Tool (VALSAT). The process cycle efficiency (PCE) value of the initial condition was equal to 5.06 %. The improvement formulations for the proposed Value Stream Mapping were made by determining optimal crew size, work-cell design, Kanban design, and idea of autonomation. The improvement formulations of the proposed Value Stream Mapping could reduce work in process (inventories) of 57.81 %, delays amounting to 55.52 %, and transportations between work stations at 52.54 %. The company’s PCE increased by 12.06 %.